2001
DOI: 10.1521/jscp.20.4.476.22397
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, Body Dissatisfaction, And Self-esteem: An Interactive Model of Bulimic Symptom Development

Abstract: The hypothesis that perfectionism, body dissatisfaction, and self-esteem interact to predict bulimic symptom development was tested. This study replicates and extends previous findings (Vohs, Bardone, Joiner, Abramson, & Heatherton, 1999) demonstrating that the joint operation of perfectionism, perceived overweight status, and low self-esteem accounts, at least in part, for bulimic symptom development. Within the context of a longitudinal design, the current study, which used different measurement approaches a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
82
2
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 39 publications
8
82
2
8
Order By: Relevance
“…13 Both low SE and body dissatisfaction have been found to correlate with higher levels of unhealthy weightcontrol behaviors and to increase the risk of developing eating disorders in adolescence. 14 The contribution of both perfectionism and SE to eating disorders has also been studied, 15 revealing that the confluence of perfectionism, body dissatisfaction, and low SE promotes development of bulimic symptoms. Specifically, perfectionists with low SE who are dissatisfied with their bodies are more likely to binge eat because they doubt their ability to lose weight, which results in negative affect and consequent increased risk of binge eating.…”
Section: Introductionmentioning
confidence: 99%
“…13 Both low SE and body dissatisfaction have been found to correlate with higher levels of unhealthy weightcontrol behaviors and to increase the risk of developing eating disorders in adolescence. 14 The contribution of both perfectionism and SE to eating disorders has also been studied, 15 revealing that the confluence of perfectionism, body dissatisfaction, and low SE promotes development of bulimic symptoms. Specifically, perfectionists with low SE who are dissatisfied with their bodies are more likely to binge eat because they doubt their ability to lose weight, which results in negative affect and consequent increased risk of binge eating.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the combination of high perfectionism, low self-efficacy, and feeling overweight was associated prospectively with greater number of weeks of binge eating. Work on a related model using self-esteem in place of self-efficacy has also found support (Holm-Denoma et al, 2005;Vohs, Bardone, Joiner, Abramson, & Heatherton, 1999;Vohs et al, 2001). Two studies using self-esteem have not replicated these interactive findings (Shaw, Stice, & Springer, 2004;Steele, Corsini, & Wade, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found each of these variables to be predictive of the later onset of bulimia nervosa symptoms. 4,5 Thus, exposure to attractive faces or thin bodies (e.g., in magazines or on television) may confer the risk for eating disorder development in women, particularly if they tend to engage in social comparison. Studies such as these document an association between exposure to attractive others and bulimia-related symptoms such as body dissa-tisfaction, but many unanswered questions remain.…”
Section: Introductionmentioning
confidence: 99%